Intended changes in smoking behaviour of Dutch young adults after an increase in excise tax: a cross-sectional survey - G Ardine de Wit; Kirsten Visscher; Babette Everaars; Anita WM Suijkerbuijk; Mattijs Lambooij (BMJ Open)
Objectives Increasing the price of tobacco is one of the most effective measures to reduce the prevalence of smoking. In the Netherlands, the excise tax on tobacco increased by €1.14 in 2020, raising the price of a standard package of cigarettes to €8.00. This study investigates how young adults intend to change their smoking behaviour in the case of hypothetical price increases of a pack of cigarettes, and which background characteristics are associated with intended behaviour change.Design A cross-sectional online survey was carried out between September and November 2020. Smokers indicated how they would react to several hypothetical increases in price. Four behavioural options were investigated: smoking less, quitting smoking, switching to another/cheaper product and buying cheaper cigarettes cross-border.Participants Data were obtained from 776 Dutch smokers between 15 and 25 years.Results At a hypothetical price of €10 per package, most respondents reported an intention to smoke less (67%), followed by switching to another/cheaper product (61%), quitting smoking (49%) and shopping for cigarettes cross-border (47%). Prior quit attempts, agreeing with the increase in excise tax and the intention to quit smoking in the future increased the odds of changing behaviour. Higher self-efficacy decreased the odds of behavioural change.Conclusion Many young adults intend to change their smoking behaviour in the event of increased prices. Although intended behaviour can deviate significantly from actual behaviour, an increase in excise tax may result in a significant amount of quit attempts and reduced smoking among young adults.